Prophylactic Use of Mitomycin-C on Haze Formation in Photorefractive Keratectomy - Awan, Abdul Hamid (Pakistan Journal of Ophthalmology, 2013)
Purpose: To study the results of prophylactic use of Mitomycin – C on corneal haze after photorefractive keratectomy (PRK). Material and Methods: Sixty – four eyes of 32 patients with myopia were enrolled in this prospective study. All patients were between the ages 20 years and 37 years with simple myopia range 6.0 D to 9.0 D. All eyes underwent PRK with application of 0.02% Mitomycin – C for 20 seconds and irrigation with 20 ml of normal saline. Patients were examined 1, 3 and 6 months after surgery. A scale of 0 to 4+ was used to grade the haze. Results: Pre-operatively, mean spherical equivalent refraction (SE) was -8.34 diopters (D) range (6.0 D to 9.50 D). All eyes were examined 1, 3 and 6 months after surgery. One month after PRK, 2 patients (3.12%) having myopia 8.5 D and above developed grade 0.5 to 1.0 haze. However, at 3 months this haze disappeared completely in one patient, whereas, the second one continued to show corneal haze grade 0.5 till 6 months postoperatively. All eyes had uncorrected visual acuity of 6/9 or better, whereas 53 eyes (82.81%) achieved uncorrected visual acuity of 6/6 or better. Conclusions: To prevent haze development in high myopia, Mitomycin – C makes a useful adjunct to Excimer laser PRK. However, further studies with a longer follow-up are required.